Lack of Smoking Effects on Pharmacokinetics of Oral Paliperidone-analysis of a Naturalistic Therapeutic Drug Monitoring Sample - Schoretsanitis, Georgios; Haen, Ekkehard; Conca, Andreas; Piacentino, Daria; Ridders, Florian; Hiemke, Christoph; Gründer, Gerhard; Paulzen, Michael (Pharmacopsychiatry, 2020)
Introduction Major smoking effects have been reported for a series of psychotropic agents, mainly including substrates of CYP450 1A2, although smoking may also affect alternative metabolic pathways. To our knowledge, smoking effects on paliperidone pharmacokinetics have not been assessed yet.Methods We compared plasma concentrations of paliperidone as well as dose-corrected-plasma concentrations (C/D) from a naturalistic database between smokers and nonsmokers using nonparametrical tests, such as the Mann-Whitney U-test (MWU). Additionally, we compared light and heavy smokers with nonsmokers separately.Results Comparing 55 smokers with 37 nonsmokers treated with oral paliperidone, no differences in the percentage of females, age, body weight, body mass index, and daily paliperidone dose were reported (p=0.709 for χ2, p=0.26, p=0.38, p=0.67, and p=0.8 for MWU). No differences were detected in plasma concentrations or C/D values (p=0.50 and p=0.96 for MWU). Likewise, differences in daily dose, plasma concentrations, or C/D values were not significant between light smokers (n=17) and nonsmokers (p=0.61, p=0.81, and p=0.33 for MWU) or heavy smokers (n=22) and nonsmokers (p=0.874, p=0.38, and p=0.59; MWU in all cases).Discussion Paliperidone is not affected by smoking, and paliperidone dose-adjustments in smokers may not be necessary. This may be seen as an essential difference to risperidone, whose cytochrome-mediated metabolism might be affected by smoking.
Keywords: Pharmacokinetics; Antipsychotic drugs; Schizophrenia treatment